1980
DOI: 10.1002/ana.410070607
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoleukodystrophy: Elevated C26 fatty acid in cultured skin fibroblasts

Abstract: Because postmortem brain and adrenal tissue from patients with adrenoleukodystrophy (ALD) or adrenomyeloneuropathy (AMN) have been shown to contain abnormally large amounts of very long chain fatty acids (C24 through C30), we searched for such an abnormality in cultured skin fibroblasts. Total lipid extracts of cultured fibroblasts were hydrolyzed, their fatty acid composition was determined by gas-liquid chromatography, and the ratio of C26 to C22 fatty acids was calculated. In 29 control cell lines this rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0
1

Year Published

1982
1982
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(85 citation statements)
references
References 24 publications
6
78
0
1
Order By: Relevance
“…The human cell lines were obtained and cultured as described by Moser et al (22). The transformed derivatives were kindly provided by Dr. S. J. Gould.…”
Section: Methodsmentioning
confidence: 99%
“…The human cell lines were obtained and cultured as described by Moser et al (22). The transformed derivatives were kindly provided by Dr. S. J. Gould.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of very long chain fatty acids in fibroblasts and plasma were measured by gas-liquid chromatography as previously described (26,27). The steps of plasmalogen biosynthesis in peroxisomes were assessed by the method of Roscher et al (28).…”
Section: Patient Selectionmentioning
confidence: 99%
“…A defect in adrenoleukodystrophy protein is known to be responsible for the X-linked neurodegeneration disorder, adrenoleukodystrophy. Adrenoleukodystrophy patient fibroblasts exhibit decreased ␤-oxidation of VLCFA, and VLCFA is accumulated in plasma and tissues (27,28). Furthermore, we have reported that PMP70 is involved in the metabolic transport of long-chain acyl-CoA across peroxisomal membranes, based on studies with CHO cells overexpressing wild-and mutant-type PMP70 (29).…”
mentioning
confidence: 99%